2022
DOI: 10.1007/s12665-022-10481-y
|View full text |Cite
|
Sign up to set email alerts
|

Validating local drivers influencing land use cover change in Southwestern Ghana: a mixed-method approach

Abstract: Addressing undesirable changes associated with the driving forces of land use cover change are critical to sustainable land management, and the future modeling of land use systems in developing countries. The study accentuates local drivers of land use cover change in Southwestern Ghana using a mixed-method approach. The approach aided in identifying key land-use drivers, using different research strategies for comparisons through confidence level analysis and Analytic Hierarchy Process. We used expert intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…All of this, combined with the phenomenon of climate change, is causing the regression of other plant formations such as shrub savannah and gallery forests. His results are similar to those obtained bySarfo et al (2022) in Southwestern Ghana who found that there is evidence of expansion in farmlands/shrubs and built-up areas over the given period. Findings based on geo-statistical analysis illustrated drastic increase in farmlands/shrubs (+369.81%) and built-up areas (+1288.36%) at the expense a reduction in forested areas (-82%), water bodies (-27%) and bare land (-18.06).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…All of this, combined with the phenomenon of climate change, is causing the regression of other plant formations such as shrub savannah and gallery forests. His results are similar to those obtained bySarfo et al (2022) in Southwestern Ghana who found that there is evidence of expansion in farmlands/shrubs and built-up areas over the given period. Findings based on geo-statistical analysis illustrated drastic increase in farmlands/shrubs (+369.81%) and built-up areas (+1288.36%) at the expense a reduction in forested areas (-82%), water bodies (-27%) and bare land (-18.06).…”
supporting
confidence: 89%
“…Thematic maps illustrating the topography and land use systems can be distinguished by interpretation of satellite imagery, using trends and conversions. Detection of LUCC using geospatial techniques is useful in supporting governmentpolicies for e cient utilisation of land (Sarfo et al, 2022).The consequences of the pressures exerted on vegetation for decades have led many researchers to take an interest in the problem of biodiversity management. In this context of strong anthropic pressure and climate change, it is urgent to evaluate the dynamics of plant communities.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental degradation is seen as the deterioration of the environment through depletion of resources which includes all the biotic and abiotic element such as air, water, soil, plants, animals, and all other living and non-living elements of planet earth that form our surroundings [1]. Sarfo, Shuoben, Otchwemah et al [2] view the key drivers of the environment as biophysical, cultural and technological factors as they have the potential of influencing climate sensitive sectors Kaledzi, [3] opined that the forest areas have shrunk five times in 100 years. Anthropogenic activities like illegal artisanal and small-scale mining, inappropriate agricultural practices, urbanization and industrialization are destroying water bodies, aquatic lives and the air we breathe [4].…”
Section: Introductionmentioning
confidence: 99%
“…These equally have the propensity to cause prolong drought, water shortage and inadequate plants and animals in the ecosystem if not managed well. Therefore, Protection of interests and concerns about climate change and observable changes in the Earth's system increase the need for further research that will improve information, innovations and informing the decision-making of urban planners, municipalities, researchers and interested organizations [2]. As warned, the natural resources underpinning the success of Ghana must be protected, sustained and managed for the future [5].…”
Section: Introductionmentioning
confidence: 99%
“…To reflect the growth status of vegetation, fractional vegetation coverage (FVC) is an important parameter for describing terrestrial ecosystems. FVC is defined as the ratio of the vertical projection area of above ground vegetation organs (including leaves, stems, and branches) to the total vegetation area (Hilker et al, 2014;Sarfo et al, 2022). The measurement methods for FVC include ground surveys and remote sensing estimation.…”
mentioning
confidence: 99%